Massive aggregation of sea star Luidia bellonae (Paxillosida: Luidiidae) in Bahía de Banderas, Jalisco, Mexican Pacific - Medina-Rosas, Pedro; Granja-Fernández, Rebeca; Galván-Villa, Cristian Moisés (Revista de Biología Tropical, 2024)
Introduction: In the central Mexican Pacific, there are few studies on asteroid ecology. These species are generally distributed randomly, although in some cases groups or aggregations can be found. In Los Arcos, south of Puerto Vallarta, in Bahía de Banderas, Mexico, Luidia bellonae was observed for the first time in a massive aggregation in 2021. Objective: To report the new record of this species in this region of the Mexican Pacific and its massive aggregation event. Methods: Transects and surveys were carried out to quantify the density and measure the sea star individuals in Los Arcos, Bahía de Banderas during 2021, 2022, and 2023. Results: Average densities of 2.65 ind/m2 and up to 7 ind/m2 were found. In total, in the approximate area of 900 m2, 630 individuals were registered. The specimens measured (R) between 2 and 12 cm, and most measured between 4 and 8 cm. Conclusions: L. bellonae has been reported in different places in some states of the Mexican Pacific; however, it was not registered for Bahía de Banderas nor Los Arcos, nor in the amount reported here, therefore this is the first record for the species with a massive presence for the Mexican Pacific. The appearance of the large number of L. bellonae specimens in Los Arcos in 2021 could have been the result of a combination of factors, including the low water temperature, with values up to 15 ºC, and the high amount of nutrients. This finding demonstrates the need for more studies on echinoderms and marine species to understand the influence of environmental conditions on their life cycle.